Cutaneous manifestations in celiac disease: An observational study - Taru Garg; Suvarna Samudrala; Praveen Kumar; Ram Chander; Sucheta Sharma (Wolters Kluwer Medknow Publications, 2023)
Background: Cutaneous manifestations associated with celiac disease (CD), other than dermatitis herpetiformis, are poorly known. The aim of the present study was to study the spectrum of dermatological disorders in children with CD. Methodology: A total of 100 cases of biopsy-confirmed CD (both new and old) were recruited after taking written informed consent/assent from the child/guardians. The patient's demographic details, history, vitals, general physical examination, systemic examination, and cutaneous examination findings were recorded. Relevant investigations were carried out, depending on the clinical findings of the cutaneous examination. Results: A total of 100 patients comprising 62 girls and 38 boys were studied, with the average age being 8.08 ± 3.67 years. Seventy patients showed the presence of dermatological findings. Cutaneous, mucosal, nail, and hair findings were seen in 35%, 7%, 14%, and 14% of patients, respectively. A higher incidence of dermatological findings was found in females (39%) compared to males (18%). The most common cutaneous conditions seen were atopic dermatitis (17%) and xerosis (10%). The most common mucosal finding was oral aphthae (4%). The most common nail changes were leukonychia and ragged cuticles (4% each). There was no statistical correlation between the presence of dermatological findings with the duration of the disease or with the duration of a gluten-free diet. Conclusion: Mucocutaneous manifestations are present in a significant proportion of patients with CD. Further studies with a larger sample size are needed to determine whether these findings are true associations or coincidental.